The facilities management standard service category / Zuraihana Ahmad Zawawi ... [et al.] - Zuraihana, Ahmad Zawawi; Wan Samsulzamani, Wan Hamdan; NurAzfahani, Ahmad; Nurul Fadzila, Zahari (2015)
In Facilities Management (FM) industry, there are a variety of requirements for different standards of service ranging from superior to basic for similar service provision. Also, there is not enough detail provided at the outset of the procurement in order for suppliers to accurately price the services required. According to Mather-Derrick (2012), the establishment of the standard service category is important to provide guidance and a framework for the development of the required scope of service to be procured and must be used when considering the options for the procurement of FM services. However, the standard service category for FM service provider in Malaysia has not been established yet. Thus, this paper is aimed to propose a FM standard service category to be as guidance in Malaysia FM industry. A set of questionnaire was designed upon literature and previous research done to gather the required information. The study is subjected to FM organizations in private sectors and only the personnel at management level are assessed. The standard categories of FM service which will be proposed are single service, bundled service, integrated facilities management, total facilities management, building-related service, user-related service and single-multi service. The identification of the appropriate standard service category is the key to the success of the delivery of FM services and a more holistic approach to the strategic decision making.